Patients' perceived needs for allied health, and complementary and alternative medicines for low back pain: A systematic scoping review - Chou, L.; Ranger, T.; Peiris, W.; Cicuttini, F.; Urquhart, D.; Briggs, Andrew; Wluka, A. (Wiley-Blackwell Publishing Ltd., 2018)
Objectives: Allied health and complementary and alternative medicines (CAM) are therapeutic therapies commonly accessed by consumers to manage low back pain (LBP). We aimed to identify the literature regarding patients' perceived needs for physiotherapy, chiropractic therapy and CAM for the management of LBP. Methods: A systematic scoping review of MEDLINE, EMBASE, CINAHL and PsycINFO (1990-2016) was conducted to identify studies examining patients' perceived needs for allied health and CAM for LBP. Data regarding study design and methodology were extracted. Areas of patients' perceived need for allied health and CAM were aggregated. Results: Forty-four studies from 2202 were included: 25 qualitative, 18 quantitative and 1 mixed-methods study. Three areas of need emerged: (i) physiotherapy was viewed as important, particularly when individually tailored. However, patients had concerns about adherence, adverse outcomes and correct exercise technique. (ii) Chiropractic therapy was perceived to be effective and needed by some patients, but others were concerned about adverse outcomes. (iii) An inconsistent need for CAM was identified with some patients perceiving a need, while others questioning the legitimacy and short-term duration of these therapies. Conclusions: Our findings regarding patients' perceived needs for allied health and CAM for LBP may assist in informing development of more patient-centred guidelines and service models for LBP. Understanding patients' concerns regarding active-based physiotherapy, which is recommended in most guidelines, and issues surrounding chiropractic and CAM, which are generally not, may help inform management that better aligns patient's perceived needs with effective treatments, to improve outcomes for both patients and the health-care system.